Fabrication Of Polysiloxane Based Stretchable Ink Filled With Silver Nanoparticles - Siew, Tuck Seong (Universiti Sains Malaysia, 2018)
Stretchable conductive ink is one of the developing technology for the recent decades. In this research, stretchable conductive composite is prepared by using polydimethylsiloxane (PDMS) as substrate and silver nanoparticles (AgNPs) as the conductive material. The ingredients used for the substrate preparation are polydimethylsiloxane-hydroxide (PDMS-OH), fumed silica, toluene, dibutyltin dilaurate and 3-glycidoxypropyl-3 trimethoxysilane. The silver conductive ink was printed on the PDMS substrate and cured at 80°C for 16 hours. Various tests have been conducted to study and investigate the electrical, mechanical and chemical properties of the PDMS-Ag composite. The PDMS-Ag sample shows low electrical resistance which reflects to good conductivity of the sample upon stretching. Furthermore, the PDMS-Ag sample shows reasonable low electrical resistance after various cycles of 50% strain stretching. Besides, the PDMS-Ag composite also displays good interfacial bonding between PDMS matrix and Ag conductive ink through the adhesion test.